The role of legitimacy in the integration of Education for Sustainable Development from the students’ perspective: A case study at the University of Nottingham - Goede, Laura (2018)
This study aims to reveal the the role that pragmatic legitimacy plays in the integration of ESD at business schools from a student's perspective. The integration of sustainability in business schools is an ongoing discussion, especially because of the notion of responsibility that business schools had for the financial crisis and continue to have for the reproduction of traditional profit-maximization thinking models. However, with the manifestation of institutions such as the PRME business schools are more and more acknowledging their role within the SD agenda. Nonetheless, integrating ESD into universities and particularly business schools due to the dominant paradigm has proven to be difficult. One part of the barriers HEIs might encounter is student resistance. Current literature when talking about student resistance is usually mentioning it conjointly with staff resistance. Also, the almost no studies in this context are focussing on legitimacy. Thus, this dissertation aims to give an indication on the connection of pragmatic legitimacy and student resistance. To explore this issues a single case study was conducted at the University of Nottingham Business School. Eight modules were interrogated using the quantitative content analysis approach to identify their integration levels complemented by a survey that was issued to all students of five different master’s degrees (target population) and examined using statistical analysis in excel to determine the level pragmatic legitimacy that is given to the concept of sustainability by students. The gathered data of the surveys and content analysis suggested the integration levels of sustainability in modules seem to have an effect on the perception of pragmatic legitimacy by students which in turn also seems to influence student resistance. For business schools that pursue a transformative ESD and that want to truly want to contribute to achieving the SDGs , this would mean that integrating sustainability into already existing courses and connecting it to course material in a meaningful way would be paramount. However, these results are not generalizable due to the small sample size obtained. This dissertation makes an original contribution to the literature dealing with the integration of ESD in HE and is providing a starting point for further research into the role of legitimacy in the resistance towards integration of ESD.